EARLY CHILDHOOD SEXUALITY EDUCATION MANAGEMENT BASED ON OUTCOME-BASED EDUCATION (OBE): HARMONIZING HIFDZUN NASL VALUES IN ISLAMIC EDUCATIONAL INSTITUTIONS - Dahlia Dahlia; Fina Umu Rif Athi (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
Sexuality education in Islamic educational institutions is frequently hindered by the stigma of “taboo” and a lack of systematic evaluation instruments. This study aims to analyze the implementation of the Outcome-Based Education (OBE) framework within the management of early childhood sexuality education at TK Aisyiyah Pembina Piyungan. Employing a qualitative approach with a case study design, data were gathered through in-depth observations, interviews, and documentation reviews, and subsequently analyzed using the interactive model of Miles, Huberman, and Saldana. The findings indicate that the planning phase successfully reformulated the curriculum by establishing measurable learning outcomes based on hifdzun nasl (safeguarding lineage and honor). In the organizing stage, the school restructured a student-centered learning ecosystem. The actuating stage was optimized through the integration of adaptive educational media, while the controlling function implemented a continuous improvement mechanism to ensure the accountability of children's self-protection competencies. This study demonstrates that no dichotomy exists between Islamic values and modern management; rather, OBE integration strengthens Islamic identity while simultaneously enhancing the professionalism of educational services.